2011
DOI: 10.1016/j.breast.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab combined to neoadjuvant chemotherapy in patients with HER2-positive breast cancer: A systematic review and meta-analysis

Abstract: The addition of trastuzumab in HER2-positive breast cancer in the neoadjuvant setting improves the probability of achieving higher pCR with no additional toxicity. Based on the available evidence, the use of trastuzumab combined with neoadjuvant chemothetherapy in patients with HER2-positive breast cancer seems to offer substantial benefit in terms of pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 25 publications
2
64
0
2
Order By: Relevance
“…1 , 2 Several studies have investigated the possibility of identifying biomarkers to distinguish patients sensitive to this therapy from those suited for novel targeted approaches. 3 Recently, analyses of gene expression profiles of tumor blocks from patients enrolled in clinical trials support a relationship between tumor dependence on HER2 signaling (HER2-E by PAM50) and trastuzumab sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Several studies have investigated the possibility of identifying biomarkers to distinguish patients sensitive to this therapy from those suited for novel targeted approaches. 3 Recently, analyses of gene expression profiles of tumor blocks from patients enrolled in clinical trials support a relationship between tumor dependence on HER2 signaling (HER2-E by PAM50) and trastuzumab sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 [13], [14] and EGFR [15], [16] and molecular therapies for other growth factor receptors are still investigational. In addition to being therapeutic targets, growth factor receptors might be useful for molecular imaging [17][19].…”
Section: Introductionmentioning
confidence: 99%
“…The study included 235 patients with locally advanced breast cancers and confirmed a beneficial effect of adding trastuzumab to chemotherapy in improving both pathological complete response (pCR) rate and survival outcomes. Subsequent studies confirmed that the addition of trastuzumab as part of neoadjuvant therapy significantly increases pCR with no additional toxicity and is currently the standard of care in this setting 52. As shown in the ACOSOG Z1041 trial, trastuzumab should be administered concurrently to taxane-based chemotherapy, while the administration with anthracyclines should be avoided 53.…”
Section: Targeted Agents For the Treatment Of Her2-positive Early-stamentioning
confidence: 96%